2021
DOI: 10.3390/vaccines9010053
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Baculovirus-Produced Grass Carp Reovirus Virus-Like Particles as Vaccine Candidate That Provides Protective Immunity against GCRV Genotype II Infection in Grass Carp

Abstract: Grass carp reovirus (GCRV) leads to severe hemorrhagic disease in grass carp (Ctenopharyngodon idella) and causes economic losses in grass carp aquaculture. Recent epidemiological investigations showed that GCRV genotype II is the dominant subtype in China. Therefore, it is very important to develop a novel vaccine for preventing diseases caused by GCRV genotype II. In this study, we employed a bac-to-bac expression system to generate GCRV-II-based virus-like particles (VLPs). Previous studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…IgZ is considered to play an important role in mucosal immunity, and it is ubiquitous in the intestine, skin, and gills ( 48 , 49 ). In previous studies, most effective vaccines induced a high level of IgM, which is critical in determining the quality of the subsequent adaptive immune response ( 11 , 39 ). In addition, effective oral vaccines can induce the production of IgZ in intestinal mucosal immunity ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgZ is considered to play an important role in mucosal immunity, and it is ubiquitous in the intestine, skin, and gills ( 48 , 49 ). In previous studies, most effective vaccines induced a high level of IgM, which is critical in determining the quality of the subsequent adaptive immune response ( 11 , 39 ). In addition, effective oral vaccines can induce the production of IgZ in intestinal mucosal immunity ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of science and technology, new vaccines against GCRV infection have been developed very rapidly ( 1 , 10 ). Among these new vaccines, both genetically engineered vaccines and subunit vaccines have been reported to be effective in protecting grass carp from GCRV infection under experimental conditions ( 11 , 12 ). However, for fish, the injectable immunization method cannot be applied on a large scale in farms due to the high cost and handling stress that may cause the mortality of vaccinated fish ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with inactivated vaccine and live‐attenuated vaccine, the recombinant subunit vaccine and DNA vaccine could effectively present antigen epitope and safely stimulate cellular and humoral immune response 176 . For recombinant subunit vaccines, the protective antigen epitopes of GCRV proteins are expressed in different expression systems such as E. coli , Bacillus subtilis , Lactococcus lactis , Saccharomyces cerevisiae and Baculovirus in vitro using recombinant DNA technology 177–181 . Research has reported that the recombinant fibre protein VP56, outer capsid proteins such as VP35 and VP7, and the inner capsid proteins such as VP3, VP4 and VP6 can effectively elicit a protective immune response against GCRV infection 49,180,182–184 .…”
Section: The Strategies To Suppress Aqrvs Infectionmentioning
confidence: 99%
“…176 For recombinant subunit vaccines, the protective antigen epitopes of GCRV proteins are expressed in different expression systems such as E. coli, Bacillus subtilis, Lactococcus lactis, Saccharomyces cerevisiae and Baculovirus in vitro using recombinant DNA technology. [177][178][179][180][181] Research has reported that the recombinant fibre protein VP56, outer capsid proteins such as VP35 and VP7, and the inner capsid proteins such as VP3, VP4 and VP6 can effectively elicit a protective immune response against GCRV infection. 49,180,[182][183][184] Interestingly, the VP4 gene of GCRV-II is divided into 4 segments and used for screening for potential antigen epitope.…”
Section: Different Types Of Vaccines Used To Against Gcrv Infectionmentioning
confidence: 99%
“…Grass carp ( Ctenopharyngodon idella ), a pivotal piscine species in the realm of aquaculture, carries considerable importance within China’s freshwater fish culture. It is distinguished by its considerable economic viability, exceptional growth performance, delectable umami meat quality, and heightened nutritional value [ 1 ]. Nonetheless as a consequence of intensive farming advancements, the emergence of disease-related challenges has become an arduous endeavor in the cultivation of grass carp [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%